POTENSI ANTIOKSIDAN FRAKSI n-HEKSANA DAUN UBI JALAR UNGU (Ipomoea batatas L.) - Fina Dwi Saadah; Denis Mery Mirza; Dian Novita Wulandari (Jurnal Kesehatan Islam : Islamic Health Journal, 2024)
ABSTRAK Antioxidants are compounds that have the advantage of neutralizing free radicals and are found in many plants. Purple sweet potato leaves (Ipomoea batatas L.) belong to the Convolvulaceae family and have potential as antioxidants due to their compound content. The n-Hexane fraction of I. batatas leaves have non-polar active compounds that have the potential to act as antioxidants such as terpenoids and steroids. This study aims to determine the active substance content and antioxidant activity in the n-Hexane fraction of I. batatas leaves. I. batatas leaves were extracted using the ultrasonic-assisted extraction method with ethanol p.a. followed by liquid-liquid fractionation using n-Hexane solvent. Identification of active compounds used phytochemical screening methods and continued testing antioxidant activity using the 2,2-diphenyl-1-picryl-hydrazylhydrate (DPPH) method with ascorbic acid as standard. The data is expressed as percent inhibition and IC50 values calculated from the linear equation. The n-Hexane fraction of I. batatas was positive for containing terpenoid compounds and has antioxidant activity of the DPPH method is in the very weak category with an IC50 value of 278,27 µg/ml compared to ascorbic acid (IC50 8,90 µg/ml) in the very strong category. The n-Hexane fraction of I. batatas leaves contains terpenoid compounds and has antioxidant activity very weak antioxidant activity with an IC50 value of 278,27 µg/mL. Keywords: Antioxidant, DPPH, Faction, Leaf I. batatas.